Epidemiological Analysis of Patients with Pre-Hospital First Aid in Keyouqian Banner, Hinggan League, Inner Mongolia - Liu W; Lu DJ; Li XW; Zhang YL; Shi MH; Wang XD (Dove Medical Press, 2022)
Wei Liu,1,* Di-Jun Lu,1,* Xiao-Wen Li,1 Yu-Liang Zhang,2 Ming-Hua Shi,2 Xu-Dong Wang1 1Department of Emergency, Aerospace Center Hospital, Beijing, 100049, People's Republic of China; 2Department of Emergency, Keyouqianqi People's Hospital, Inner Mongolia, 137400, People's Republic of China*These authors contributed equally to this workCorrespondence: Xu-Dong Wang, Department of Emergency, Aerospace Center Hospital, No. 15 of Yuquan Street, Haidian District, Beijing, 100049, People's Republic of China, Tel +86 10 59971968, Fax +86 10 59971199, Email xudongwang59@163.comObjective: To summarize the characteristics of patients calling the 120 emergency number for pre-hospital first aid in Keyouqian Banner, Hinggan League.Methods: The clinical data of adult patients with pre-hospital first aid from 2016 to 2018 were retrospectively analyzed.Results: There were 2711 cases with pre-hospital first aid. Males significantly outnumbered females. Young and middle-aged patients comprised 81.5%. Patients were mainly Han and Mongolians. Most injuries and illnesses occurred at home and on the road. The time to arrival of medical services was 30.34 ± 28.29 minutes. The proportion of pre-hospital first aid for trauma was the highest, followed by diseases concerning the cardiovascular and neurological systems. The proportion of patients with improved medical conditions after onsite first aid was 43.3%, the proportion with unchanged conditions was 51.7%, and the total mortality rate was 3.9%.Conclusion: The disease spectrum, ethnic distribution, age at onset, and pre-hospital first aid capabilities for outpatients were analyzed. These results may facilitate the establishment of a pre-hospital first aid system for the local prevention and control of acute and critical illnesses, increase the success rate of the region's pre-hospital first aid services, and improve the prognosis.Keywords: Keyouqian Banner, Inner Mongolia, pre-hospital first aid, emergency medical service, epidemiological analysis